Enhancement of ductile deformation in polycrystalline anorthite due to the addition of water. (March 2022) - Fukuda, Junichi; Muto, Jun; Koizumi, Sanae; Sawa, Sando; Nagahama, Hiroyuki
Abstract: We performed shear deformation experiments on synthetic anorthite (An) aggregates with various amounts of water added externally. The samples were pure An aggregates and aggregates of An with 5% Si–Al-rich glass (An + glass hereafter), each with up to 0.5 wt% added water. The experiments were conducted using a Griggs-type deformation apparatus at 900 °C and 1.0 GPa, with shear strain rates ranging from 10 −3.5 to 10 −5.0  s −1 . We observed a clear reduction of up to two orders of magnitude in effective viscosity with an increase in the amount of added water. Microstructural observations indicate that the deformation behavior evolves from brittle to ductile with an increasing amount of added water. The pure An sample with 0.5 wt% added water is more than an order of magnitude stronger than the equivalent An + glass sample. Infrared spectroscopy measurements reveal that the water contents trapped in the An + glass and pure An samples increase up to 1710 and 840 ppm H2 O, respectively, during the 0.5 wt% added-water experiments. The difference in the water contents of the two samples indicates that approximately half of the water content is trapped in glass. Graphical abstract: Image 1 Highlights: Up to 0.5 wt% water was externally added to polycrystalline anorthite. Added water reduces sample strength of up to two orders of magnitude. Ductile deformation is enhanced by the added water and presence of glass. Trapped water is held in grain boundaries and glass. Strain weakening can be associated with the development of strain localization.